2023
DOI: 10.3389/fcimb.2023.1117987
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of metagenomic next-generation sequencing in sepsis and bloodstream infection

Abstract: ObjectiveTo evaluate the diagnostic value of metagenomic next-generation sequencing (mNGS) in sepsis and bloodstream infection (BSI).MethodsA retrospective analysis of patients diagnosed with sepsis and BSI at the First Affiliated Hospital of Zhengzhou University from January 2020 to February 2022 was conducted. All the patients underwent blood culture and were divided into mNGS group and non-mNGS group according to whether mNGS was performed or not. The mNGS group was further divided into early group (&lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Previous studies had already demonstrated that the mNGS can improve the prognosis by guiding targeted antibiotic treatment with high sensitivity and specificity. 7 , 8 However, fewer clinical studies have verified the diagnostic accuracy and detection time of ONT sequencing. 13 And there was no clinical study exploring the consistency between ONT sequencing with the clinical diagnosis in patients with SHAP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had already demonstrated that the mNGS can improve the prognosis by guiding targeted antibiotic treatment with high sensitivity and specificity. 7 , 8 However, fewer clinical studies have verified the diagnostic accuracy and detection time of ONT sequencing. 13 And there was no clinical study exploring the consistency between ONT sequencing with the clinical diagnosis in patients with SHAP.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also demonstrate that the pathogenesis for the syndrome can be determined even in cases with negative results from the bacterial culture. In fact, even if endophthalmitis is suspected clinically and the culture yields negative results, treatment for endophthalmitis is often continued until clinical findings improve 11–13 21. If the metagenome yields positive results in culture-negative cases, it can serve as a basis for continuing the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…While WGS aims to analyse the genome of a single bacterium, 16S rRNA metagenomic analyses and shotgun metagenomics are used to comprehensively determine bacterial compositions in clinical specimens 7–10. Metagenomic analysis effectively detects pathogens responsible for systemic infectious diseases such as sepsis, pneumonia and urinary tract infection; in a short period of time and with high positivity rates 11–13. If pathogens are detected in the early stage of sepsis, proper selection of antibiotics for treatment can reduce the mortality rate 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include bacterial colony concentration, peptide nucleic acid fluorescence in situ hybridization (PNA FISH), and direct antimicrobial susceptibility testing (AST) from positive blood cultures [3]. Innovation extends even further with the adoption of emerging technologies that bypass the culture process entirely, such as polymerase chain reaction (PCR) on whole blood samples [4], T2 magnetic resonance technology [5], and next-generation sequencing (NGS) [6,7]. NGS, a large-scale DNA sequencing technology, still faces delays in producing results but amplicon-based sequencing has already improved its timeline, indicating the potential for similar advancements in whole genome sequencing techniques.…”
Section: From Human Skill To Machine Precisionmentioning
confidence: 99%